Data, Information, and Governance of Digital Climate-Informed Advisory Services - Born, Lorna; Bucher, Ana; Hansen, James; Prager, Steven D.; Rose, Alison; Zebiak, Stephen E. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This paper presents the findings of a working group that was assembled to support drafting of the Blueprint for Digital Climate-Informed Advisory Services: Building the Resilience of 300 million Small-Scale Producers by 2030. This working group, which focused on data and governance, met every two weeks from June to August 2020 to collect information and feedback through consultation sessions and short questionnaires. A full list of Working Group 1 members is included in Appendix 1. A longer version of this working paper was submitted as an input into the Blueprint. The Blueprint was a collaborative effort with the following partners: World Resources Institute (WRI), the Global Center on Adaptation (GCA), the International Research Institute for Climate and Society at Columbia University (IRI), the World Food Programme (WFP), and the World Business Council on Sustainable Development (WBCSD). The goal of achieving climate resilience for 300 million small scale producers requires a variety of climate risk management strategies for agriculture. Climate services and agricultural advisory services are strategies that are supported by decades of research, institution building, investment and experience. The use of ICT has been integral to these services for years but has recently shown rapid acceleration. However, several widespread and persistent challenges confront efforts to integrate climate services, advisory services and digital innovation to increase climate resilience. Investments should target those gaps that threaten to limit achieving impactful digital agro-advisory services (DCAS), with recognition that past efforts, current initiatives and the capacity of relevant actors vary by country. Investment is key in the digital tools and innovations that are needed to support farmer decision-making and the various institutions that provide information and guidance to farming communities. Simultaneous investment is necessary in the enabling environment allowing for DCAS to achieve an impact. The enabling environment is a particular focus as the development of digital solutions depends on the policies, institutions and capacities prevalent in a context. The following are key aspects of the general enabling environment that should be addressed in endeavours to invest in and improve DCAS and its contribution to small scale producers’ climate resilience: • Construction and maintenance of national data systems that ascribe to data governance standards, allowing for the creation of coherence among the multiple providers of information and advice • Monitoring, evaluation, learning and co-production of improved services, with accountable partnership between public and private sector actors • Building of farmer capacity for access, use and driving co-production of DCAS, while recognizing that complementary non-digital communication channels could avoid disadvantaging farmers that face barriers to accessing digital delivery channels • Garnering sufficient public commitment and sustainable public goods investment, establishing viable business models, and gathering supporting evidence to sustain impact at scale • Provision and effective use of high-quality data and derived information, partly through addressing any gaps in the data collection and management systems of the public meteorological, agricultural and environmental information on which quality DCAS depend • Extending DCAS investment to support other agricultural value chain actors whose capacity to manage climate risk significantly impacts small scale producers